PELANGGARAN HAK MORAL KARYA LAGU/ MUSIK DAN REKAMAN SUARA DALAM PRAKTIK PENGGUNAAN HAK CIPTA - Andre Pratista, I Gusti Putu; Sukihana, Ida Ayu (Kertha Semaya : Journal Ilmu Hukum, 2014)
The absence of explicit recognition of moral rights element in a work song/music and voice recordings in the regulation of Copyright, proved to have a weaker impact at the same disregard for the rights of paternity and the right of integrity. Conversely, a prominent and gain recognition as well as an all-out fight for their enforcement is Economic Rights. Images of such conditions reflect the character of Copyright law as an instrument of economic right heavy. Meanwhile, the conception of Copyright protection can not be separated from the cultural rules and norms of local wisdom inherent in a work song / music and sound recordings. However, so many cases of violations of moral rights in a work song / music and sound recording is reviewed, it is more understood merely as a violations of ethics. The purpose of this paper is to determine the shape of infringement in addition Moral Rights to a work song / music and sound recordings, in the form of infringement of Integrity and Attribution Rights. Another aim was to determine the law enforcement efforts and measures that can be performed in the enforcement of moral rights has begun to neglect and lose their enforcement by the Economic Rights of a work song / music and sound recordings that can be overcome with some effort as institutional strengthening copyright, dissemination and awareness-raising law society and legal action against infringement of moral rights.
Keywords: Moral Rights, Violations, Copyright